Imagining the Balkans: Identities and Memory in the Long 19th Century: Reviewing National Ideas Through a Regional Exhibition Project. Issue 1 (21st June 2016) - Mazarakis‐Ainian, Philippos
Abstract: The UNESCO travelling exhibition Imagining the Balkans was a cooperation project between 12 History museums of South East Europe, which set out to review the negative stereotypes and antagonistic readings of nation‐building in the region. Although it proved a very fruitful experience for those involved, it faced a series of potentially crippling challenges, when parts of it were perceived by authorities or by the public as 'subversive'. Its interest resides mainly in the fact that it is the first attempt at a joint presentation of historical phenomena to the region's general public. The thematic storyline emphasises commonalities among the peoples, and tries to create implicit occasions for interaction with the visitor's identity, images of the past, and present experiences.